Patient Experienced Continuity of Care in the Psychiatric Healthcare System—A Study Including Immigrants, Refugees and Ethnic Danes - Jensen, Natasja Koitzsch (MDPI, 2014)
Aim: The purpose of this study was to investigate continuity of care in the psychiatric healthcare system from the perspective of patients, including vulnerable groups such as immigrants and refugees. Method: The study is based on 19 narrative interviews conducted with 15 patients with diverse migration backgrounds (immigrants, descendents, refugees, and ethnic Danes). Patients were recruited from a community psychiatric centre situated in an area with a high proportion of immigrants and refugees. Data were analysed through the lens of a theoretical framework of continuity of care in psychiatry, developed in 2004 by Joyce et al., which encompasses four domains: accessibility, individualised care, relationship base and service delivery. Results: Investigating continuity of care, we found issues of specific concern to immigrants and refugees, but also commonalities across the groups. For accessibility, areas pertinent to immigrants and refugees include lack of knowledge concerning mental illness and obligations towards children. In terms of individualised care, trauma, additional vulnerability, and taboo concerning mental illness were of specific concern. In the domain of service delivery, social services included assistance with immigration papers for immigrants and refugees. In the relationship base domain, no differences were identified. Implications for priority area: The treatment courses of patients in the psychiatric field are complex and diverse and the patient perspective of continuity of care provides important insight into the delivery of care. The study highlights the importance of person-centred care irrespective of migration background though it may be beneficial to have an awareness of areas that may be of more specific concern to immigrants and refugees. Conclusions: The study sheds light on concerns specific to immigrants and refugees in a framework of continuity of care, but also commonalities across the patient groups.